Influence of the Ambient Storage of LiNi0.8Mn0.1Co0.1O2 Powder and Electrodes on the Electrochemical Performance in Li-ion Technology - Iratxe de Meatza; Imanol Landa-Medrano; Susan Sananes-Israel; Aitor Eguia-Barrio; Oleksandr Bondarchuk; Silvia Lijó-Pando; Iker Boyano; Verónica Palomares; Teófilo Rojo; Hans-Jürgen Grande; Idoia Urdampilleta (Batteries, 2022)
Nickel-rich LiNi0.8Mn0.1Co0.1O2 (NMC811) is one of the most promising Li-ion battery cathode materials and has attracted the interest of the automotive industry. Nevertheless, storage conditions can affect its properties and performance. In this work, both NMC811 powder and electrodes were storage-aged for one year under room conditions. The aged powder was used to prepare electrodes, and the performance of these two aged samples was compared with reference fresh NMC811 electrodes in full Li-ion coin cells using graphite as a negative electrode. The cells were subjected to electrochemical as well as ante- and postmortem characterization. The performance of the electrodes from aged NM811 was beyond expectations: the cycling performance was high, and the power capability was the highest among the samples analyzed. Materials characterization revealed modifications in the crystal structure and the surface layer of the NMC811 during the storage and electrode processing steps. Differences between aged and fresh electrodes were explained by the formation of a resistive layer at the surface of the former. However, the ageing of NMC811 powder was significantly mitigated during the electrode processing step. These novel results are of interest to cell manufacturers for the widespread implementation of NMC811 as a state-of-the-art cathode material in Li-ion batteries.